Index-Based Livestock Insurance policy workshop: Comments from participants - International Livestock Research Institute (International Livestock Research Institute, 2015)
Highlights of participants comments from an Index-Based Livestock Insurance (IBLI) policy workshop held 9 June 2015 at ILRI in Nairobi.